PENGGUNAAN KONSEP RULES IN USE OSTROM DALAM ANALISIS PERATURAN PEMBENTUKAN ORGANISASI KESATUAN PENGELOLAAN HUTAN - Eno Suwarno; Hariadi Kartodihardjo; Lala M Kolopaking; Sudarsono Soedomo (Jurnal Analisis Kebijakan Kehutanan, 2015)
Following  the establishment  of Forest Management Units (KPHL/KPHP) by the Indonesian  Ministry of Forestry, the next step that has to be done  is the  formation and operationalization of KPHL/KPHP organization by local  governments. In reality, implementation of the respective obligation is stagnated due to a number of obstacles such as the regulatory aspects that haveless trust and difficult to be implemented by local governments. In the Institutional Analysis and Development (IAD Framework) from Elinor Ostrom, there is onecomponent, i.e. the rules-in-use concept that is possible to be applied as a tool  to analyze the relationship between the content of a certain regulation and the structure of action-situation formed due to implementationof regulation.This study aimsto test  effectiveness of  the  use  of the  concept  of  rules-in-use  to find  substantial  shortcomings  of  the  regulation  on  KPHL/KPHP formation at  provincial  level,as  a basisforimprovement. Accordingly,  analysis  was  performed  on  PP  No.6/2007  jo.  PPNo.3/2008,  Permendagri  No.61/2010  and  PP  No.41/2007by  making  analysis  of  regulation  contents and  feedback  from the implementation  process.  Based  on  the  results  of  this  study,  it  can  be  concluded  that  the  use  of  Ostrom's  rules-in-use  concept  is adequately effective to find the shortcomings of KPHL/KPHP regulation content.